MEDIA EDUKASI PANDUAN MANDIRI REHABILITATIF PADA KLIEN DIABETES MELITUS TIPE 2 DI WILAYAH PUSKESMAS CINUNUK - Nurrani Putri Riyaddudin; Atin Karjatin (Politeknik Kesehatan Kemenkes Bandung, 2025)
Background: According to SKI 2023, the number of people with Diabetes Mellitus in West Java has increased, including in Bandung Regency, which recorded 62,344 clients. Cinunuk Public Health Center is one of the subdistricts with the highest number of cases, totaling 2,307 clients. The large number of clients indicates the need for rehabilitative efforts to prevent decreased productivity and more severe complications. Educational media is needed as a tool to improve knowledge and control health-related behaviors, thereby preventing higher morbidity rates. Objective: To develop a self-guided rehabilitative educational media using the Research and Development (R&D) method with the 4D approach model. Method: The development stages included define, design, develop (involving expert validation in content and media, small-scale trial), and a quantitative evaluation using a quasi-experimental one group pre-test post-test design on 40 respondents, followed by dissemination. Results: Clients require a printed educational media in the form of a self-guided booklet containing rehabilitative materials and a behavioral monitoring table. The developed media showed a positive impact on clients’ knowledge. The media was also disseminated via QR code and link through WhatsApp and print distribution. Conclusion: The rehabilitative self-guided educational media is feasible for use as a strategy to support rehabilitative behavioral control in clients with type 2 Diabetes Mellitus.